2016
DOI: 10.1111/bjh.14331
|View full text |Cite
|
Sign up to set email alerts
|

Similar incidence of severe acute GVHD and less severe chronic GVHD in PBSCT from unmanipulated, haploidentical donors compared with that from matched sibling donors for patients with haematological malignancies

Abstract: SummaryThe features of graft-versus-host disease (GVHD) were compared between patients who underwent myeloablative conditioning and received a peripheral blood stem cell transplant (PBSCT) from either a haploidentical donor (HID) or a matched sibling donor (MSD) during the same period of time. The HID group included more patients with advanced disease. Both groups received the same GVHD prophylaxis with the addition of antithymoglobulin (ATG) in HID group. Higher cumulative incidences (CI) of acute GVHD grade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 21 publications
(36 reference statements)
2
19
0
Order By: Relevance
“…The incidences of DLI-associated acute GVHD grades 2–4, 3–4, chronic GVHD, and NRM in our study were 55.3%, 10.2%, 52.0,%, and 33.1%, respectively. In the patients who received haplo-PBSCT in our unit before January of 2015 [ 14 ], the incidences of acute GVHD grades 2–4, 3–4, chronic GVHD, and NRM were 36.1%, 14.5%, 38.4%, and 24.0%, respectively. Though the incidences of GVHD between these two cohort studies should not be compared directly, it seemed that G-PB DLI did not result in an intolerable toxicity in terms of GVHD and NRM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidences of DLI-associated acute GVHD grades 2–4, 3–4, chronic GVHD, and NRM in our study were 55.3%, 10.2%, 52.0,%, and 33.1%, respectively. In the patients who received haplo-PBSCT in our unit before January of 2015 [ 14 ], the incidences of acute GVHD grades 2–4, 3–4, chronic GVHD, and NRM were 36.1%, 14.5%, 38.4%, and 24.0%, respectively. Though the incidences of GVHD between these two cohort studies should not be compared directly, it seemed that G-PB DLI did not result in an intolerable toxicity in terms of GVHD and NRM.…”
Section: Discussionmentioning
confidence: 99%
“…All recipients received G-PB as a source of graft. The supportive therapy was done as previously described [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…The incidence of Epstein-Barr virus (EBV) and cytomegalovirus (CMV) antigenemia and EBV-associated post-transplantation proliferative disease (PTLD) was higher in patients receiving stem cells from haploidentical donors compared with that of patients receiving MSD-PBSCT. Donor age ≥ 40 years vs. younger donors was associated with a higher incidence of aGVHD grades 2-4 (P = 0.02) and treatment-related mortality (TRM) (P = 0.022) [4].…”
Section: Introductionmentioning
confidence: 99%
“…There is an urgent need to reduce the incidence of severe cGVHD and improve the quality of life in patients who have undergone MSD peripheral blood stem cell transplantation (MSD-PBSCT) [3]. We have reported that rabbit anti-thymocyte globulin (rATG) (Sanofi, Paris, France) may effectively and safely reduce the incidence and severity of cGVHD in patients receiving myeloablative conditioning before peripheral blood stem cell transplantation from haploidentical donors [4]. The 3-year cumulative incidence of extensive and severe cGVHD was 41.5% and 21.2% in patients receiving MSD-PBSCT (without rATG) compared with 17.1% (P = 0.017) and 5.8% (P = 0.049) in patients receiving stem cells from haploidentical donors [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation